Unpublished Letters - Mariátegui, José Carlos (Universidad del Pacífico, 1980)
On the fiftieth anniversary of his death (April 16, 1930), José Carlos Mariátegui is undoubtedly one of the most significant politicians and intellectuals of modern Peru. We face today, however, a necessary work to review his work, an urgent review of its interpretations of the specific problems of the social reality of this country. We offer this set of letters, kindly provided by the Mariátegui family in the assurance that they will help to support a more solid an real knowledge of the man and his work. The six letters have been selected from the compilation "José Carlos Mariátegui, Correspondence", prepared by the publisher Amauta, that will include, in more than one volume, the letters from Mariátegui that were collected to date, and some letters received by him, according to their importance.